GROWTH AND ENERGY QUALITY OF EUCALYPTUS WOOD IN DIFFERENT CROP-LIVESTOCK-FOREST SPATIAL ARRANGEMENTS - tonini, helio; Morales, Marina Moura; Wruck, flavio Jesus; Deliberali, Ronaldo Maran (Floresta, 2020)
The aim of the present study was to assess the growth and energetic properties of genetic material of eucalyptus grown in several integrated crop-livestock system spatial arrangements in Barra-do-Garças City (MT). The genetic material of 76-month old Eucalyptus spp from eight spatial arrangements were assessed according to the following properties: diameter, height and volume growth, mortality rate, dry matter yield, sapwood to heartwood ratio, form factor, bark volume, basic density, superior calorific value, ash content, volatile matter, fixed carbon and trunk energy. Data analysis was performed by adjusting growth function, test for model identity and parameters equality and ANOVA tests to Scott-Knott’s mean clustering test. Eucalyptus grandis x E. urophylla clones from recorded the highest energy efficiency due to their high yield volume, which was decisive to determine estimated energy available per tree and cropland area. Growth, stem shape and basic density varied among, and within, the same genetic materials, depending on their respective spatial arrangement. However, solid biomass properties (high calorific value, ash content, fixed carbon and volatile matter) remained stable.